When the Corn Grows Tall in Texas : a Story of the Texas Revolution - McDonald, Archie P.; Peacock, Joe (Austin, Tex. : Eakin Press, 1991)
In the winter of 1836 eight-year-old Albert sees his father ride off to help fight the Mexican soldiers and secure independence for Texas.
Keywords: Texas - History -- Revolution, 1835-1836; Juvenile literature -- Fiction; Texas -- History -- Revolution, 1835-1836; Texas -- History -- Revolution, 1835-1836